Advances in cartography and GIScience : selections from the International Cartographic Conference 2017 - Peterson, Michael P. (Springer International Publishing : Imprint : Springer, 2017)
This book presents a selection of manuscripts submitted to the 2017 International Cartographic Conference held in Washington, DC at the beginning of July and made available at the conference. These manuscripts have been selected by the Scientific Program Committee and represent the wide-range of research that is done in the discipline. It also forms an important international collection representing research from at least 30-40 countries.
Keywords: Geographic information systems -- Congresses.; Cartography -- Congresses.; elektronické knihy; electronic books